Arctic storm [large type] - Sundell, Joanne (Watch eyes trilogy, 2015)
In 1908, thirteen-year-old Anya, a Chukchi shaman, will do anything to protect the sled dogs she has raised so she joins forces with sixteen-year-old seafarer Rune Johansson to make a stand against phantom predators hiding in the Arctic West as a powerful ice storm brews.